Dynamic changes of the pelvic floor in elite athletes of different sports. - Pires,Telma (2020)
Abstract Introduction: One of the functions of the pelvic floor muscles (PFM) is to support the pelvic organs and continence. This continence mechanism tends to change when PFM are exposed to high-impact exercises. Objetives: To describe the dynamic changes in the pelvic floor (PF) in elite nulliparous athletes. Methods: Translabial two and three-dimensional ultrasound was used to assess PF anatomy and function in athletes (n=8). This ultrasonography was performed after voiding and in the supine position, using a vaginal probe. The descent of the pelvic organs was assessed on a maximum Valsalva maneuver, whilst the volume datasets were acquired at rest, during maximum voluntary contraction (MVC) and during a Valsalva maneuver. The athletes performed each maneuver at least 3 times, with the most effective being used for evaluation. Results: The bladder neck descent was 14 mm for the javelin thrower, being the highest value when compared to the remaining participants. Three athletes featured the rectocele (swimming, gymnastics and javelin throw) and 4 participants presented a paravaginal defect (volleyball, horsemanship, javelin throw and printer). The volleyball athlete had the highest value of the levator hiatal area in MVC value. Conclusions: The athletes present minimal differences in the evaluated parameters. The sample is small to generalize the results, but there is a tendency for athletes of high-impact exercises to have a lower CMV value. Further studies are needed to corroborate these results.